2019
DOI: 10.1007/s10854-019-02422-6
|View full text |Cite
|
Sign up to set email alerts
|

Scientific complications and controversies noted in the field of CdS/CdTe thin film solar cells and the way forward for further development

Abstract: Cadmium telluride-based solar cell is the most successfully commercialised thin film solar cell today. The laboratory-scale small devices have achieved ~ 22%, and commercial solar panels have reached ~ 18% conversion efficiencies. However, there are various technical complications and some notable scientific contradictions that appear in the scientific literature published since the early 1970s. This review paper discusses some of these major complications and controversies in order to focus future research on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…PEC Cell Measurement for electrical conductivity type. CdTe on its own shows p-type electrical conductivity when grown with Te-richness 16 . Hence, during electrodeposition, CdTe changes its conduction type from p to n, due to the greater incorporation of cadmium at larger cathodic voltages surpassing Te.…”
Section: Structural Study Using X-ray Diffraction (Xrd) Technique Stmentioning
confidence: 99%
See 1 more Smart Citation
“…PEC Cell Measurement for electrical conductivity type. CdTe on its own shows p-type electrical conductivity when grown with Te-richness 16 . Hence, during electrodeposition, CdTe changes its conduction type from p to n, due to the greater incorporation of cadmium at larger cathodic voltages surpassing Te.…”
Section: Structural Study Using X-ray Diffraction (Xrd) Technique Stmentioning
confidence: 99%
“…It has been conceptualised by our group that, GBG devices can be constructed based on two approaches in terms of the electronic conduction type of the window material; i) fabricated on n-type window and ii) fabricated on p-type window. Though our current highest efficiency for CdTe-based GBG solar cells are achieved from n-window devices, cells fabricated on p-type windows have a potential to achieve higher performance due to the possibility of producing higher open circuit voltage (V oc ) resulted from a higher potential barrier 15 , 16 . This has been experimentally demonstrated by achieving Voc ≈ 1.17 V with GaAs/AlGaAs and Voc ≈ 1.00 V with Perovskite based solar cells 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that thermal treatment creates Cd vacancies (V Cd ) that could facilitate the substitution of metal atoms in the Cd sub-lattice (M Cd ). 52,53 Both V Cd and M Cd create acceptor-like energy states located at E v + 0.13 eV and E v + 0.22 eV above the valence band, 54 respectively. Moreover, the thermal treatment also improves the film's crystalline quality as seen in XRD and SEM images in the previous section and also reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] R.H. Bube and others carried out further analysis of CdS/CdTe‐based photovoltaic heterojunction cells and obtained an efficiency value of 8.4%. [ 5 ] In 1980, Tyan Yuan Sheng of Eastman Kodak Company established different fabrication techniques for polycrystalline CdTe‐based solar cells with an efficiency of 8.9%. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%